The Impact of Privacy and Data Protection Policies on Digital Marketing Strategies in The Lazada Application (Case Study on Students of University of Tribhuwana Tunggadewi, Malang, Management Study Program Class of 2021 And 2022) - Elisabeth Ariyati Bui; Moch. Nurhidayat; Yuni Setyawati (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this study was to determine the impact of privacy policies and data protection on digital marketing strategies in the Lazada application on students of Tribhuwana Tunggadewi University, Malang, Management Study Program, Class of 2021 and 2022. The type of research used was quantitative. The determination of the sample for this study used saturated sampling so that the research sample was 50 respondents. The data collection steps used by the researcher were questionnaires. The data analysis technique was multiple linear regression analysis using the SPSS program. The results of the study prove that privacy policies have a significant effect on the performance of digital marketing strategies in the Lazada application on students of Tribhuwana Tunggadewi University, Malang, Management Study Program, Class of 2021 and 2022, which means that students as digital users who are aware of the importance of data protection, give a positive response to the privacy policy implemented. Data protection does not have a significant effect on the performance of digital marketing strategies in the Lazada application for students of Tribhuwana Tunggadewi University Malang Management Study Program Class of 2021 and 2022, which means that although privacy policies are important for protecting user data, most students do not make it the main factor in assessing the effectiveness of digital marketing strategies.